Prospective, Head-to-Head Study of Three Computerized Neurocognitive Assessment Tools (CNTs): Reliability and Validity for the Assessment of Sport-Related Concussion. (30th December 2015) - Nelson, Lindsay D.; LaRoche, Ashley A.; Pfaller, Adam Y.; Lerner, E. Brooke; Hammeke, Thomas A.; Randolph, Christopher; Barr, William B.; Guskiewicz, Kevin; McCrea, Michael A.
Abstract: Limited data exist comparing the performance of computerized neurocognitive tests (CNTs) for assessing sport-related concussion. We evaluated the reliability and validity of three CNTs—ANAM, Axon Sports/Cogstate Sport, and ImPACT—in a common sample. High school and collegiate athletes completed two CNTs each at baseline. Concussed ( n =165) and matched non-injured control ( n =166) subjects repeated testing within 24 hr and at 8, 15, and 45 days post-injury. Roughly a quarter of each CNT's indices had stability coefficients ( M =198 day interval) over .70. Group differences in performance were mostly moderate to large at 24 hr and small by day 8. The sensitivity of reliable change indices (RCIs) was best at 24 hr (67.8%, 60.3%, and 47.6% with one or more significant RCIs for ImPACT, Axon, and ANAM, respectively) but diminished to near the false positive rates thereafter. Across time, the CNTs' sensitivities were highest in those athletes who became asymptomatic within 1 day before neurocognitive testing but was similar to the tests' false positive rates when including athletes who became asymptomatic several days earlier. Test–retest reliability was similar among these three CNTs and below optimal standards for clinical use on many subtests. Analyses of group effect sizes, discrimination, and sensitivity and specificity suggested that the CNTs may add incrementally (beyond symptom scores) to the identification of clinical impairment within 24 hr of injury or within a short time period after symptom resolution but do not add significant value over symptom assessment later. The rapid clinical recovery course from concussion and modest stability probably jointly contribute to limited signal detection capabilities of neurocognitive tests outside a brief post-injury window. ( JINS, 2016, 22, 24–37)